Ampliación de la distribución de Mesoscincus schwartzei (Squamata: Scincidae) en el estado de Chiapas, México - Percino-Daniel, Ruth; Barcenas Arriaga, Sergio; Sarabia Rangel, Adrián (Instituto de Ecología, A.C., 2012)
We report Mesoscincus schwartzei from Playón de la Gloria, Chiapas, México. One individual was found underneath a fallen tree in tropical rain forest. Previously, this species was only known from the Peninsula de Yucatán, including the northern portions of Petén, Guatemala, and Belize. This new record expands its known distribution 78.5 km to the south.